Controlled free radical polymerization in miniemulsion using Reversible Addition-Fragmentation Chain Transfer (RAFT) - Vosloo, Johannes Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2001.